Hematological malignancy-associated pyoderma gangrenosum: evaluating the magnitude of the association - Kridin, Khalaf; Ankary-Khaner, Moria; Kridin, Mouhammad; Cohen, Arnon D.; Badarny, Samih (Frontiers in Medicine, 2024)
Background: Hematologic malignancies (HMs) are well-known underlying comorbidities of pyoderma gangrenosum (PG). However, studies quantifying the likelihood of PG after HMs are yet to be performed.To investigate the bidirectional association between PG and several HMs, namely acute leukemia, chronic leukemia, Hodgkin lymphoma, non-Hodgkin lymphoma, and multiple myeloma.Methods: A population-based retrospective cohort study was conducted to study the risk of HMs in patients with PG (n=302) as compared to age-, sex-and ethnicity-matched control subjects (n=1,799). A casecontrol design was used to estimate the likelihood of PG in individuals with a preexisting history of HMs.Adjusted hazard ratios (HRs) and adjusted odds ratios (ORs) were estimated by Cox regression and logistic regression, respectively.The prevalence of preexisting HM was higher in patients with PG than in controls (6.7% vs. 0.9%, respectively). The likelihood of having PG was significantly greater among patients with a history of HM (adjusted OR, 7.88; 95% CI, 3.85-16.15; P<0.001), particularly during the first year following the diagnosis. This association was significant for acute leukemia, chronic leukemia, non-Hodgkin lymphoma, and multiple myeloma but not for Hodgkin lymphoma. The incidence rate of HM was 3.3 (95% CI, 1.2-7.4) and 1.6 (95% CI, 0.9-2.6)/1,000 person-years among patients with PG and controls, respectively. Relative to controls, patients with PG were not more likely to develop subsequent HM (adjusted HR, 2.22; 95%CI, 0.77-6.45; P=0.142). Compared to other patients with PG, those with HM-associated PG experienced an increased all-cause mortality rate (adjusted HR, 2.19; 95%CI, 1.09-4.40; P=0.028).Conclusions: HM, particularly acute leukemia and multiple myeloma, are associated with an elevated likelihood of provoking PG.